2018
DOI: 10.1016/j.cpr.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of suicide ideation and behaviors among transgender people: A systematic review guided by ideation-to-action theory

Abstract: Transgender people are at high risk for suicide ideation, attempts, and deaths compared to the general population. Several correlates of suicide ideation and attempts have been identified empirically to understand this increased risk. However, few attempts have been made to systematically review this literature. Further, a theory to understand and identify targetable factors for intervention has rarely been applied to this population. In the first systematic review guided by ideation-to-action frameworks of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 47 publications
2
50
0
11
Order By: Relevance
“…For instance, a recent systematic review of discrimination and mental health concluded that heterosexist prejudice, compared to racial prejudice, was most influential on SRB among sexual and gender minority (SGM) Black persons [48]. Also, another review of transgender and gender minority suicide showed that multiple marginalized statuses pertaining to race and religion were uniquely important factors among gender diverse persons [49]. Thus, we examined the SRB risk and protective factor patterns for the following set of marginalized identities among members of the alternative sexuality community: race, sexual orientation, gender, education level, and ethnicity.…”
Section: Relationship Orientation Marginalized Identity and Preferementioning
confidence: 99%
“…For instance, a recent systematic review of discrimination and mental health concluded that heterosexist prejudice, compared to racial prejudice, was most influential on SRB among sexual and gender minority (SGM) Black persons [48]. Also, another review of transgender and gender minority suicide showed that multiple marginalized statuses pertaining to race and religion were uniquely important factors among gender diverse persons [49]. Thus, we examined the SRB risk and protective factor patterns for the following set of marginalized identities among members of the alternative sexuality community: race, sexual orientation, gender, education level, and ethnicity.…”
Section: Relationship Orientation Marginalized Identity and Preferementioning
confidence: 99%
“…However, 20 address the issue primarily among youth or children; as secondary or incidental to another issue (e.g., HIV), a single aspect of a larger topic (e.g., transgender health); or among sexual minorities writ large (e.g., LGBT). The five meta-analyses and systematic reviews that primarily assessed SITBs among transgender adults are Marshall et al, 116 Virupaksha et al, 117 McNeil et al, 118 Wolford-Clevenger et al, 119 and Adams et al 3 Two 116,118 account for review parameters (exclusion of gray literature) but fail to identify a number of studies and, in one case, count a single data set multiple times. One 117 includes gray literature, but only selects articles freely available online and relevant to the review title, without explaining how the latter was systematized.…”
Section: Introductionmentioning
confidence: 99%
“…One 117 includes gray literature, but only selects articles freely available online and relevant to the review title, without explaining how the latter was systematized. One 119 identifies factors (attempts, behavior, and deaths) correlated with transgender SITBs in literature published between 1991 and January 2017 but does not analyze data on SITBs in this literature. One 3 presents an earlier stage of this research, which excludes literature published since February 2016 and does not focus on the impact of ethnicity, income, or education on SITBs.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the past decade have empirical studies of suicide risk and resilience in transgender veterans been conducted. Extant work has focused primarily on understanding the prevalence of STBs in this population, with less attention to risk and resiliency factors (Wolford-Clevenger, Frantell, Smith, Flores, & Stuart, 2018). The lack of research is unsurprising given that transgender individuals were not able to openly serve in the military without fear of discharge until 2016, when DoD instruction (DoDI) 1300.28 and directive-type memorandum 16-005 were issued (U.S.…”
Section: Suicide Risk and Resilience Factors In Transgender Veteransmentioning
confidence: 99%
“…Candidate factors to study in the transgender veteran population could include clinical (e.g., onset of SI, plans for SI, risk-taking behaviors; Nock et al, 2018), individual-difference (pain tolerance and fearlessness of death; Joiner, 2005), and practical factors (access to and familiarity with means for suicide; Klonsky & May, 2015). A recent systematic review of static and dynamic suicide risk factors identified in the broader transgender suicide literature used the ideation-to-action framework as its guiding theoretical lens (Wolford-Clevenger et al, 2018). This review identified predictors of SA history that may also serve as factors that facilitate the transition from suicidal thoughts to behaviors (although none were tested in this manner in the extant literature).…”
Section: Suicide Risk and Resilience Factors In Transgender Veteransmentioning
confidence: 99%